Application of diffuse reflectance near-infrared spectrometry and chemometrics in characterization of micro and mesoporous ZSM-5 zeolites. Issue 61 (10th October 2018) - Amani, Shahin; Garmarudi, Amir Bagheri; Khanmohammadi, Mohammadreza; Yaripour, Fereydoon
Abstract : Evaluation of porosity type of zeolites is one of the critical topics in catalysis science. Abstract : Evaluation of porosity type of zeolites is one of the critical topics in catalysis science. The relationship between external surface area and diffuse reflectance (DR) spectra in the near-infrared spectral region has been employed to propose a method for estimation of micro or mesoporosity in ZSM-5 zeolite samples. Linear discriminant analysis (LDA) was utilized to estimate degree of porosity based on near-infrared diffuse reflectance spectra. The textural properties (surface area and pore volume) of micro and mesoporous ZSM-5 samples were measured using N2 adsorption/desorption technique at 77 K and external surface area was calculated by t -plot as a reference method in this work. Several porous ZSM-5 samples with only microporous channels or mesoporous besides them were classified in terms of external surface area and meso pore volume derived from t -plot as "Micro" or "Micro + Meso" type samples. It was concluded that LDA using the PCA for feature selection is capable of generalization and could precisely predict the type of porosity in ZSM-5 zeolites.